Fish fin-clips as a non-lethal approach for biomonitoring of mercury contamination in aquatic environments and human health risk assessment - Cerveny, Daniel; Roje, Sara; Turek, Jan; Randak, Tomas (Chemosphere, 2016)
Muscle tissue and pectoral fins of two important indicator fish species, frequently used in biomonitoring programs, were sampled and analysed for total mercury content (THg) at six localities within the Czech Republic. The relationship between mercury concentration in muscle and in fin-clips was described. Mean values of THg fin-clip concentration correlate significantly (p < 0.01) with those measured in muscle of indicator fish. Concerning comparison among localities, a coefficient of determination (r(2)) of 0.85 and 0.91 was found between studied approaches in the case of chub (Squalius cephalus) and bream (Abramis brama), respectively. THg muscle concentrations (mean, n = 10) varied from 0.181 to 0.491 μg g(-1) wet, depending on indicator species and locality. A concentration-dependent relationship between muscle and fin-clip THg content was found in both species. Based on this finding, a novel method for the prediction of muscle THg concentration from fin-clips analysis was developed. The difference between measured and predicted muscle concentration was below 10% in both indicator species at most sampling sites. Use of fish fin-clips was found as an appropriate nonlethal approach for the evaluation of mercury contamination in aquatic environments as well as for human health risk assessment.
Keywords: monitorování životního prostředí; Bream; Česká republika; Risk Assessment; Environmental Monitoring; regresní analýza; Muscles; Cyprinidae; rtuť; Czech Republic; chemické látky znečišťující vodu; Mercury; Water Pollutants, Chemical; Prediction; hodnocení rizik; zvířata; Animal Fins; Humans; svaly; Muscle; ploutve zvířat; Fishes; Chub; Regression Analysis; ryby; Health risk; Hg; lidé; Animals